2008
DOI: 10.2320/matertrans.f-mra2008835
|View full text |Cite
|
Sign up to set email alerts
|

Surface Hardening of Cast Irons by Friction Stir Processing

Abstract: A new surface hardening technology for cast irons was developed by applying the Friction Stir Processing (FSP) in which the matrix can be controlled in the solid state. Flake graphite cast iron (FC300) and spheroidal graphite cast iron (FCD700) were used to investigate the validity of this new method. As a result, it has been clarified that a Vickers hardness of about 700 HV is obtained for both the flake graphite cast iron and the spheroidal graphite cast iron, and that the hardness depends on the size and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Fujii et al 10) reported the possibility of martensitic transformation emerging in FCD700 (ductile cast iron) and FC300 (gray cast iron) after FSP. To gain a further understanding, this study aims at clarifying the microstructural features introduced by FSP pertaining to the improvement in erosion wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Fujii et al 10) reported the possibility of martensitic transformation emerging in FCD700 (ductile cast iron) and FC300 (gray cast iron) after FSP. To gain a further understanding, this study aims at clarifying the microstructural features introduced by FSP pertaining to the improvement in erosion wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Yamaguchi et al 65,66 performed a novel surface treatment on flake graphite cast iron (FC300) and nodular graphite cast iron (FCD700) and found that, as shown in Figure 23, very fine martensite microstructure was formed in both flake graphite cast iron and nodular graphite cast iron and hardness in the range of 700-900 HV was obtained. If it is remembered that the hardness of the base metal is 200 HV, then the hardening effect is much greater than that in aluminium and it is on the basis of these results that the application of this technique to the fabrication of cast structures of machine tools, etc., was considered possible.…”
Section: Friction Stir Processingmentioning
confidence: 95%
“…911) The authors clarified that the pearlite-based cast iron, such as FC300 and FCD700, can be hardened due to the formation of fine martensite by the FSP. 12,13) However, the main phase of these materials is pearlite. There is no report about the surface hardening of ferrite-based cast iron.…”
Section: Introductionmentioning
confidence: 99%